Myths about the feminization of agriculture: Implications for global food security - Kawarazuka, Nozomi; Doss, Cheryl R.; Farnworth, Cathy Rozel; Pyburn, Rhiannon (Elsevier, 2022)
The term “feminization of agriculture” is used to describe changing labor markets that pull men out of agriculture, increasing women's roles. However, simplified understandings of this feminization persist as myths in the literature, limiting our understanding of the broader changes that affect food security. Through a review of literature, this paper analyses four myths: 1) feminization of agriculture is the predominant global trend in global agriculture; 2) women left behind are passive victims and not farmers; 3) feminization is bad for agriculture; and 4) women farmers all face similar challenges. The paper unravels each myth, reveals the complexity of gendered power dynamics in feminization trends, and discusses the implications of these for global food security.